2020
DOI: 10.1038/s41467-019-14206-x
|View full text |Cite
|
Sign up to set email alerts
|

Observation of extremely efficient terahertz generation from mid-infrared two-color laser filaments

Abstract: Extreme nonlinear interactions of THz electromagnetic fields with matter are the next frontier in nonlinear optics. However, reaching this frontier in free space is limited by the existing lack of appropriate powerful THz sources. Here, we experimentally demonstrate that two-color filamentation of femtosecond mid-infrared laser pulses at 3.9 μm allows one to generate ultrashort sub-cycle THz pulses with sub-milijoule energy and THz conversion efficiency of 2.36%, resulting in THz field amplitudes above 100 MV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
139
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(141 citation statements)
references
References 59 publications
2
139
0
Order By: Relevance
“…In 2020, Koulouklidis et al demonstrated two-color filamentation of femtosecond mid-infrared laser pulses at 3.9 μm generating ultrashort [68] sub-cycle THz pulses with sub-milijoule energy. The results showed THz conversion efficiency of 2.36%, resulting in THz field amplitudes above 100 MV cm − 1 [75].…”
Section: Optimization Of Thz Systemmentioning
confidence: 96%
“…In 2020, Koulouklidis et al demonstrated two-color filamentation of femtosecond mid-infrared laser pulses at 3.9 μm generating ultrashort [68] sub-cycle THz pulses with sub-milijoule energy. The results showed THz conversion efficiency of 2.36%, resulting in THz field amplitudes above 100 MV cm − 1 [75].…”
Section: Optimization Of Thz Systemmentioning
confidence: 96%
“…Dey et al [59] demonstrated enhanced broadband intense THz generation by filamentation in liquids, with about 1 µJ/pulse/THz and spanning from~0.1 to 50 THz (see the dark gray plot in Figure 1c. Recently, Koulouklidis et al [60] proposed an extremely brilliant THz source by two color filamentation of MIR laser pulses with the fundamental wavelength set to 3.9 µm. Conversion efficiency above 2% and electric fields of more than 100 MV/cm were demonstrated spanning between ca.…”
Section: Introductionmentioning
confidence: 99%
“…Powerful terahertz radiation sources have attracted considerable attention due to their applications in many fields of science [1][2][3], such as THz spectroscopy of condensed matter or biological issues [4][5][6], nonlinear THz optics [7], and resonant control of materials [8,9]. Conventional laser-based THz radiation sources include optical rectification from nonlinear crystals [10][11][12], two-color laser filamentation [13,14], and switched photoconducting antennnas [15]. The peak fields are limited to the order of a few MV/cm, and the radiation energies are smaller than 1 mJ.…”
Section: Introductionmentioning
confidence: 99%